Perlindungan Nasabah Bank Syariah BUMN Pasca Merger Ditinjau Berdasarkan Hukum Perseroan Terbatas dan Hukum Perbankan - Mirza Alvina Maharani; Aam Suryamah; Agus Suwandono (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2022)
A merger is the merge of two or more banks, by maintaining the establishment of one bank and dissolving the other banks with or without liquidating as stated in Law no. 10 of 1998 concerning Amendments to Law no. 7 of 1992 concerning Banking. Mergers carried out by a company must take into account the interests of the company, minority shareholders, employees of the company, creditors, and other business partners of the company as well as the community and healthy competition in doing business as this is mandated in Law no. 40 of 2007 concerning Limited Liability Companies. As a result of the merger of BUMN Sharia Banks, it affects many things, including the Company itself, Bank Customers, Shareholders, and other Creditors who are directly or indirectly related to the merging bank. Therefore, the purpose of this study is to analyze the legal consequences and legal protection for customers after the merger of state-owned Islamic banks. The approach method used is normative juridical, data obtained from a literature study. Based on the results of the study, it can be concluded that the merger of BUMN Syariah Banks resulted in the merging companies, namely PT Bank Syariah Mandiri (BSM) and PT BNI Syariah (BNIS) end because the law was effective from the date of the merger. The dissolution of BSM and BNIS occurred without any prior liquidation. The end of the legal entity status of the merging company is also followed by the transfer of assets and liabilities of the merging company to the merging company. The transfer of assets and liabilities resulted in the shareholders of the merging Company legally becoming the Company's Shareholders who received the Merger, but with voting rights and share conversion agreed upon by the parties involved. According to the Indonesian banking legal system, legal protection for depositors can be carried out in 2 (two) ways, namely implicit and explicit protection, and the existence of a Deposit Insurance Corporation (LPS) which guarantees deposits belonging to depositors in bank mergers.